Use of response surface methodology for partitioning, one-step purification, of alkaline extracellular lipase from Penicillium candidum (PCA 1/TT031) - Alhelli, Amaal M.; Abdul Manap, Mohd Yazid; Mohammed, Abdulkarim Sabo; Mirhosseini, Hamed; Suliman, Eilaf; Shad, Zahra; Mohammed, Nameer Khairullah; Meor Hussin, Anis Shobirin (Elsevier BV, 2016)
This report shows the partitioning and purification of alkaline extracellular lipase from Penicillium candidum (PCA 1/TT031) by solid-state fermentation (SSF). In the present analysis, some of the important parameters such as PEG concentration, PEG molecular mass, salt concentration and buffer concentration were optimised through the response surface methodology (RSM). The optimum aqueous two-phase systems (ATPS) environment consisted of 13.8% (w/w) phosphate buffer, 9.2% (w/w) PEG-3000 and 3.3% (w/w) NaCl at 25°C. The RSM approach was proved to be the most suitable methodology for the recovery of desired enzymes. In this method, the enzyme partitioned into the top phase of the PEG-buffer-NaCl ATPS. Under this experimental environment, the purification factor was found to be 33.9, the partition coefficient was 4.0 and the yield was found to be 84.0% of lipase. Moreover, the experimental and predicted results were in considerable agreement, which established the reliability and validity of the proposed model. The ATPS methodology is proven to be effective for the primary recovery of lipase at a low cost with a large loading capacity and possibility of linear scale up. In addition to using the existing methodologies for improving enzyme production, the use of statistical optimisation of the constituents of phases through RSM continues to be the basic and practical method.